Inventory and function of yeast ABC proteins: about sex, stress, pleiotropic drug and heavy metal resistance - Bauer, B.E.; Wolfger, H.; Kuchler, K.
Saccharomyces cerevisiae was the first eukaryotic organism whose complete genome sequence has been determined, uncovering the existence of numerous genes encoding proteins of the ATP-binding cassette (ABC)family. Fungal ABC proteins are implicated in a variety of cellular functions, ranging from clinical drug resistance development, pheromone secretion, mitochondrial function, peroxisome biogenesis, translation elongation, stress response to cellular detoxification. Moreover, some yeast ABC proteins are orthologues of human disease genes, which makes yeast an excellent model system to study the molecular mechanisms of ABC protein-mediated disease. This review provides a comprehensive discussion and update on the function and transcriptional regulation of all known ABC genes from yeasts, including those discovered in fungal pathogens.
Keywords: FUNGUS; ABC PROTEIN; PDR NETWORK; GENE REGULATION; ANTIFUNGAL DRUG RESISTANCE; PATHOGEN; PHEROMONE SECRETION; ORGANELLE; STRESS RESPONSE; CELLULAR DETOXIFICATION